2009
DOI: 10.1007/s12026-009-8115-8
|View full text |Cite
|
Sign up to set email alerts
|

Diverse immune mechanisms may contribute to the survival benefit seen in cancer patients receiving hyperthermia

Abstract: There is increasing documentation of significant survival benefits achieved in cancer patients treated with hyperthermia in combination with radiation and/or chemotherapy. Most evidence collected regarding the mechanisms by which hyperthermia positively influences tumor control has centered on in vitro data showing the ability of heat shock temperatures (usually above 42 degrees C) to result in radio- or chemosensitization. However, these high temperatures are difficult to achieve in vivo, and new thermometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 89 publications
(108 reference statements)
2
58
0
2
Order By: Relevance
“…2A, B). These findings may indicate that the anti-tumor activity caused by single hyperthermia was mainly due to activation of the immune system, 20) but not to a direct tumor-killing effect. In a previous study, the activation of both caspase-8 and 9 was found to mediate the enhancement of tumor necrosis factor (TNF)-induced apoptosis in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 85%
“…2A, B). These findings may indicate that the anti-tumor activity caused by single hyperthermia was mainly due to activation of the immune system, 20) but not to a direct tumor-killing effect. In a previous study, the activation of both caspase-8 and 9 was found to mediate the enhancement of tumor necrosis factor (TNF)-induced apoptosis in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 85%
“…The disadvantages are systemic stress and a limitation to <42°C due to thermosensitivity of critical tissues like heart, liver and brain. Thus the thermal goals of systemic therapy are usually more modest than local heating techniques, and intended for activation of drugs (48) or enhancement of immunologic response (49)(50)) rather than radiosensitization. When heating the whole body, normal body-cooling mechanisms such as respiration and skin cooling must be blocked by thermally insulating the patient and preheating the breathing circuit.…”
Section: Whole Body Heatingmentioning
confidence: 99%
“…Mild elevation of temperature favours the cells to readjust the homeostatic equilibrium [5]. Fever appears to be an evolutionarily conserved response to bacterial or viral infection and may have survival benefits [6]. Again, when an individual is exposed to temperature above the zone of thermal neutrality, heat appears as a stress and changes occur in different physiological systems, such as cardiovascular, respiratory, endocrines, neural etc.…”
Section: Introductionmentioning
confidence: 99%